Morphology of the immature stages and notes on the natural history of the little-known plume moth Stenoptilodes juanfernandicus Gielis (Lepidoptera: Pterophoridae) - Espinoza-Donoso, Sebastián; Parra, Luis E.; González-Espinoza, Cristóbal; Vargas-Ortiz, Marcelo; Vargas, Héctor A. (Zootaxa, 2018)
Stenoptilodes juanfernandicus Gielis, 1991 (Lepidoptera: Pterophoridae) was described from the Juan Fernandez Islands, Chile; it was subsequently recorded from the Galápagos Islands and mainland Ecuador. Its larva and pupa are described and illustrated for the first time with the aid of light and scanning electron microscopy. Descriptions are based on specimens collected as larvae displaying cryptic coloration feeding on inflorescences of Verbena hispida Ruiz & Pav. (Verbenaceae) in the Andes of northern Chile. Several differences were found with the larva and pupa of congeneric representatives, suggesting that immature morphology should be further explored to assess its value in the taxonomy and systematics of Stenoptilodes Zimmerman, 1958. Verbena hispida is the first host plant recorded for S. juanfernandicus, a finding that will be helpful to further explore different Neotropical environments to better characterize the geographic range of this plume moth.